IDENTIFYING EFL STUDENTS’ MOTIVATION TOWARDS READING ACTIVITY TO ENRICH THE CLASSROOM INTERACTION IN ELT CONTEXT - Ikrar Genidal Riadil (Universitas Mahaputra Muhammad Yamin, 2020)
Motivation is an inner condition that guides human behaviors towards a certain target. Motivation for learning is massively important, because the greater motivation that they have gained, the greater the learning outcomes of the learners. This research was done in the sense of low interaction in the classroom as learners seldom read a book, especially before attending to the lesson. The purpose of this research was therefore to discover the motivation of the students in reading activity to enrich the classroom interaction in learning English as a foreign language (EFL). The researcher used descriptive qualitative approach. Firstly, the study, first, the researcher looked for the questionnaire of motivation to read. Secondly, the researcher selected the constructs or in this term, the questions categories to be used in this study. Thirdly, the researcher spread the selected questions as a questionnaire to the students of fifth semester of English Department in Tidar University. Then, after the researcher had finished collecting the data, the researcher analyzed the data acquired by demonstrating the motivation of the students to read the literature review. Eventually, the researcher reported the results on the basis of the study evidence.